Epilepsie dospělých - Vojtěch, Zdeněk (Triton, 2000)
Informační publikace o epilepsii dospělých.
Vím víc ; sv. 3
Keywords: epilepsie; antikonvulziva; Status Epilepticus; Epilepsy; Anticonvulsants; status epilepticus; neurologie